Story : substance, structure, style, and the principles of screenwriting. - McKee, Robert, ....- (New York : Harper Collins, 1997)
A guide to the art of screenwriting explains how to develop a storyline, refine a work in progress, and do other key aspects of creating works for film.
Keywords: Scenario's.